2021
DOI: 10.7759/cureus.13973
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Temporal Artery True Fusiform Aneurysm With Several Lateral Feeding Vessels

Abstract: Brummund et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…We included 45 studies in the present systematic review after full-text screening [Figure 3]. [1,5,[7][8][9][10][11][12][13][14]17,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]36,[38][39][40][41][42][43][44][45][46][47]49,55,57,58,[61][62][63] According to the systematic review, 63 cases, including the present case, were identified after Brown first reported pathologically confirmed nontraumatic true STAA in 1942. All of the data acquired following the standardized form are shown in Supplementary Tables 1 and 2.…”
Section: Search Resultsmentioning
confidence: 99%
“…We included 45 studies in the present systematic review after full-text screening [Figure 3]. [1,5,[7][8][9][10][11][12][13][14]17,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]36,[38][39][40][41][42][43][44][45][46][47]49,55,57,58,[61][62][63] According to the systematic review, 63 cases, including the present case, were identified after Brown first reported pathologically confirmed nontraumatic true STAA in 1942. All of the data acquired following the standardized form are shown in Supplementary Tables 1 and 2.…”
Section: Search Resultsmentioning
confidence: 99%